Novel Mitochondria-Targeted Furocoumarin Derivatives as Possible Anti-Cancer Agents - Mattarei, Andrea; Romio, Matteo; Managò, Antonella; Zoratti, Mario; Paradisi, Cristina; Szabò, Ildikò; Leanza, Luigi; Biasutto, Lucia (Frontiers in Oncology, 2018)
Targeting small molecules to appropriate subcellular compartments is a way to increase their selectivity and effectiveness while minimizing side effects. This can be accomplished either by stably incorporating specific “homing” properties into the structure of the active principle, or by attaching to it a targeting moiety via a labile linker, i.e., by producing a “targeting pro-drug”. Mitochondria are a recognized therapeutic target in oncology, and blocking the population of the potassium channel Kv1.3 residing in the inner mitochondrial membrane (mtKv1.3) has been shown to cause apoptosis of cancerous cells expressing it. These concepts have led us to devise novel, mitochondria-targeted, membrane-permeant drug candidates containing the furocoumarin (psoralenic) ring system and the triphenylphosphonium (TPP) lipophilic cation. The strategy has proven effective in various cancer models, including pancreatic ductal adenocarcinoma, melanoma and glioblastoma, stimulating us to devise further novel molecules to extend and diversify the range of available drugs of this type. New compounds were synthesized and tested in vitro; one of them – a prodrug in which the coumarinic moiety and the TPP group are linked by a bridge comprising a labile carbonate bond system – proved quite effective in in vitro cytotoxicity assays. Selective death induction is attributed to inhibition of mtKv1.3. This results in oxidative stress, which is fatal for the already-stressed malignant cells. This compound may thus be a candidate drug for the mtKv1.3-targeting therapeutic approach.